Opening the Pipeline to the Field of Communication Sciences and Disorders Through Career Counseling. - Castro, Nichol (Perspectives of the ASHA Special Interest Groups, 2025)
Purpose: The field of communication sciences and disorders (CSD) has increased its efforts to recruit more students, particularly students with historically marginalized backgrounds, into our professions. Recommendations have been provided in the literature for doing this work; however, an underexplored aspect of recruitment in CSD is career counseling. The purpose of this study was to understand the current state of career counseling for CSD professions. Method: A survey was completed by current graduate students in CSD programs to understand their experiences with career counseling, including how they learned about the field of CSD. Results: About 40% of participants did not receive any kind of career counseling, and only about 30% of participants received career counseling specific to CSD. Those who did not receive career counseling tended to be individuals with a direct connection to the field (e.g., a family member was a clinician, they received or knew someone who received services). Those who did receive career counseling tended to be more diverse in race and ethnicity than the current professional body. Despite different career counseling experiences, most participants expressed a need for more career counseling in undergraduate and graduate programs. Conclusions: Collaboration with career counselors may provide an opportunity to expand recruitment efforts in the field of CSD, particularly when recruiting students with historically marginalized backgrounds who do not have a direct connection to the field. Career counseling is a long-standing field of practice and research. CSD professionals can help inform career counselors' practice by increasing awareness of our field and professions, as well as learn ways to provide career counseling through programmatic education and experiences in their departments.